Common trunk of the internal thoracic artery, inferior thyroid artery and thyrocervical trunk from the subclavian artery: a rare arterial variant - Westrych, Karolina; Ruzik, Kacper; Zielinska, Nicol; Paulsen, Friedrich; Georgiev, Georgi P.; Olewnik, Lukasz; Labetowicz, Piotr (Surgical and Radiologic Anatomy, 2022)
Purpose In this article, we describe a complex and rare variant of the common trunk arising as a branch of the subclavian artery. This description highlights the clinical relevance of such a variation for medical practice. Methods A routine dissection was carried out on an adult 74-year-old female cadaver. After identification and preparation of the common trunk, measurements and photographs were taken. Results The dissection revealed a common trunk arising from the first part of the left subclavian artery. It divided into the left internal thoracic artery, the inferior thyroid artery, and the thyrocervical trunk. Further on, the branches of the thyrocervical trunk supplied blood to the trapezius muscle, the longus colli muscle and the supraspinatus muscle. Conclusion For the first time, we report the specific appearance of a common trunk from the left subclavian artery that includes the origin of the left internal thoracic artery, inferior thyroid artery, and thyrocervical trunk. Knowledge of the different variations of subclavian branches is essential because of the high frequency with which this region is involved in diagnostic and surgical procedures.
CRIS-Team WoS Importer:2022-07-15